Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/jbm.b.34970
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical in vitro fatigue testing of implant materials and components using advanced characterization techniques

Abstract: Implants of different material classes have been used for the reconstruction of damaged hard and soft tissue for decades. The aim is to increase and subsequently maintain the patient's quality of life through implantation. In service, most implants are subjected to cyclic loading, which must be taken particularly into consideration, since

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
(158 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the reduction of closure force was proportional to the number of times a clip was reused. This was likely due to the nonelastic deformation of the aneurysm clip after repetitive opening, which occurred when the clip deformation exceeds its tensile yield strain and depends on its materials [13,33]. Papadopoulos et al examined the effects of repeated use on the closure force of titanium alloy Yaşargil clips and pure titanium Spetzler clips and found that the closure force of both Yaşargil and Spetzler clips were weakened by a 10-min sustained maximal opening [34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reduction of closure force was proportional to the number of times a clip was reused. This was likely due to the nonelastic deformation of the aneurysm clip after repetitive opening, which occurred when the clip deformation exceeds its tensile yield strain and depends on its materials [13,33]. Papadopoulos et al examined the effects of repeated use on the closure force of titanium alloy Yaşargil clips and pure titanium Spetzler clips and found that the closure force of both Yaşargil and Spetzler clips were weakened by a 10-min sustained maximal opening [34].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in fatigue strength of implant materials when exposed to corrosion conditions is equally well known 3,4 . There are, however, very few reports of in vitro simulations of the effect of body fluids on the fatigue characteristics of implants manufactured by AM or directed energy deposition (DED) techniques 5,6 . Wegner et al 5 investigated laser powder bed fusion magnesium alloy implants in an in vitro environment, along with ultra‐high molecular weight polyethylene (UHMWPE) and titanium implants.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 There are, however, very few reports of in vitro simulations of the effect of body fluids on the fatigue characteristics of implants manufactured by AM or directed energy deposition (DED) techniques. 5,6 Wegner et al 5 investigated laser powder bed fusion magnesium alloy implants in an in vitro environment, along with ultra-high molecular weight polyethylene (UHMWPE) and titanium implants. Their intention was to develop and demonstrate that an in vitro test set-up reduced the time necessary to perform fatigue characterization.…”
Section: Introductionmentioning
confidence: 99%